Improving the water-resistance of MgO-based metal–insulator–metal capacitors by inserting a BeO thin film grown via atomic layer deposition. Issue 17 (13th April 2022) - Wang, Bo Wen; Kim, Seungsoo; Song, Haewon; Seo, Haengha; Li, Xiangyuan; Choi, Jin Myung; Choi, Jinwoo; Shin, Jonghoon; Hwang, Cheol Seong
Abstract : To improve the water-resistance of MgO-based metal–insulator–metal capacitors, BeO/MgO/BeO/MgO/BeO stacked layers were deposited by atomic layer deposition using bis(cyclopentadienyl)magnesium and diethyl beryllium and O3 as an oxygen source. Abstract : To improve the water-resistance of MgO-based metal–insulator–metal (MIM) capacitors, BeO/MgO/BeO/MgO/BeO (BMBMB) stacked layers with a total thickness of ∼10 nm (2/2/2/2/2 nm) were deposited at 335 °C by atomic layer deposition (ALD) using bis(cyclopentadienyl)magnesium [Mg(Cp)2 ] and diethyl beryllium (DEB) as Mg and Be precursors, respectively, and O3 as an oxygen source. High-quality MgO and BeO single films were produced under optimized ALD conditions. The bottom electrode was a sputtered 50 nm-thick TiN layer, and a 10/30 nm-thick TiN/Pt layer served as the top electrode. The adoption of BeO layers in the insulator stack enabled excellent water-resistance, while the MgO-based capacitor suffered from severely degraded electrical performance during water exposure. Moreover, the capacitors with BeO layer insertion showed a significantly reduced leakage current density ( J ) to ∼10 −9 A cm −2 at an applied bias of +0.8 V even without further annealing treatment during the aggressive water immersion test. Even with a relatively low k of the inserted BeO layer, the equivalent oxide thickness (EOT) could be further decreased to ∼3.5 nm for the 10 nm-thick BMBMB stacked layer, which was similar to the EOT value of the single MgO film with identical thickness. The chemical composition, interface properties, chemical bonding, and crystallization behaviors were comparatively studied for single and stacked layers. This work demonstrated that the BMBMB thin film stack could be a desirable moisture and leakage current blocking layer in recent electronic devices with nanoscale dimensions.